RISK FACTORS FOR CHYLE LEAK AFTER ESOPHAGECTOMY - Batool, Sadaf; Akbar, Sana Amir; Khan, Misbah; Sayyed, Raza; Shakeel, Osama; Syed, Aamir Ali; Khattak, Shahid; Khan, Ali Raza (Journal of Ayub Medical College Abbottabad, 2019)
Background: Chylothorax is an uncommon (3-8% risk) but potentially fatal complication of esophagectomy with poorly understood risk factors. It has a high morbidity due to loss of fluids, electrolytes, and other nutrients, loss of lymphocytes and immune dysfunction. Methods: Retrospective chart review of adult patients who underwent esophagectomy between 2009 and 2016 was performed. Cases with chyle leak were identified according to a set criteria. Clinical features, operative findings and postoperative variables were recorded and predictors of chyle leak were analyzed. Results: During the study period, a total of 193 adult patients underwent esophagectomy of which 186 received neo adjuvant chemotherapy. The mean age was 53 years with 118 males and 74 females. Type of procedure performed was 3-stage esophagectomy in 98, Transhiatal esophagectomy in 79 and Ivor-Lewis esophagectomy in 15 patients. Chyle leak was identified in 9 (4.6%) patients. There was no significant association of chyle leak with age, gender, co-morbid, level of tumor, Neo-adjuvant therapy and Type of esophagectomy. Chest drain output on postoperative day 5 was significantly predictive of chyle leak (p-value<0.05). Drain output more than 1000 on day 4 was highly suggestive of chyle leak (p-value<0.05). Day on which chest drain was removed was also found to be significantly related to chyle leak (p-value <0.05). Conclusion: No significant preoperative risk factors were identified for chyle leak. High chest drain output on postoperative day 5 and drain output more than 1000 on day 4 are significant predictors of chyle leak. Keywords: Thoracic duct; chylothorax; chylous ascites; chest drain